1985
DOI: 10.1111/j.1399-3054.1985.tb02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root restriction on growth correlations, water relations and senescence of alder seedlings

Abstract: Root restriction may be of importance for productivity in both forestry and agriculture. To study the physiological effects of root restriction in European alder (Alnus glutinosa Gaertn.), seedlings were grown in aerated liquid culture under one of four root volumes to induce the following levels of root restriction: 1.5, 6,16 and 500 ml. Root restriction for 96 days reduced shoot elongation, plant dry weight, leaf area and chlorophyll levels and increased leaf area/root dry weight ratio and correlative bud in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 33 publications
4
38
0
4
Order By: Relevance
“…Selon rouge B une production de plants de plus fortes dimensions. Tschaplinski et Blake (1985), les parois paforks qui permettent Dans la prtsente ttude, c'est effectivement le contenant de cerner les plants en dirigeant les racines vers l'exttrieur, Whitcomb 3 500 qui possae le plus haut rapport surface 1 proinduisent un dtveloppement racinaire en amont du cernage. fondeur.…”
Section: Effets Du Repiquage Sur La Croissance Des Ch6nesunclassified
“…Selon rouge B une production de plants de plus fortes dimensions. Tschaplinski et Blake (1985), les parois paforks qui permettent Dans la prtsente ttude, c'est effectivement le contenant de cerner les plants en dirigeant les racines vers l'exttrieur, Whitcomb 3 500 qui possae le plus haut rapport surface 1 proinduisent un dtveloppement racinaire en amont du cernage. fondeur.…”
Section: Effets Du Repiquage Sur La Croissance Des Ch6nesunclassified
“…Wang et al (2001) reported that water stress occurred almost every day in plants subjected to root restriction, because the amount of available water was reduced. Several reports have suggested that the reduction in shoot growth due to root restriction is partly attributed to disturbance of the internal water relations (Tschaplinski and Blake, 1985;Arp, 1991). Garg et al (2001) reported that increasing water stress progressively decreased plant growth potential, leaf area, net photosynthetic rate and nitrate reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Green-house studies concerning the effects of rooting depth on tree growth have mostly focused on depth restriction imposed by the presence of a compacted layer on the growing medium (e.g., Misra and Gibbons 1996) or by reduced pot size (e.g., Tschaplinski and Blake 1985). In the first case, depth restriction is not absolute and depends on the ability of the root system to grow into the compacted layer.…”
Section: Introductionmentioning
confidence: 99%